INDETERMINATE DOMAIN–DELLA protein interactions orchestrate gibberellin-mediated cell elongation in wheat and barley - Patrycja Sokolowska; Matthias Jöst; Wolfram Buss; Brett Ford; Peter Michael Chandler; Wolfgang Spielmeyer; Andrew L. Phillips; Alison K. Huttly; Danuše Tarkowská; Rocío Alarcón-Reverte; Suzanne J. Clark; Stephen Pearce; et al. (Proceedings of the National Academy of Sciences, 2026)
DELLA proteins, members of the GRAS-domain family of transcriptional regulators, play a crucial role in plant growth and development. They modulate transcription indirectly via interactions with hundreds of transcription factors. The phytohormone gibberellin (GA) triggers DELLA degradation, providing a mechanism by which plants can integrate developmental and environmental signals to regulate gene expression and optimize growth responses. In agriculture, DELLA mutations have been instrumental in improving crop performance. Most modern wheat ( Triticum aestivum L.) varieties carry Rht-B1b or Rht-D1b alleles that encode DELLA proteins resistant to GA-mediated degradation, resulting in constitutive partial suppression of stem growth, a semi-dwarf stature, and lodging resistance. However, these alleles also reduce early vigor and nitrogen use efficiency, limiting their utility in some environments. Understanding how DELLA proteins regulate growth and development is, therefore, critical for refining breeding strategies. In this study, we identified the orthologous C2H2 zinc-finger transcription factors INDETERMINATE DOMAIN 5 ( IDD5 ) in wheat and SEMI-DWARF 3 ( SDW3 ) in barley ( Hordeum vulgare ) as positive regulators of stem and leaf expansion. Both IDD5 and SDW3 physically interact with, and act downstream of, DELLA proteins as key components of GA-mediated growth responses. Altered expression levels of GA biosynthesis genes suggest that IDD5 contributes to GA homeostasis in addition to growth regulation. Loss-of-function mutations in IDD5 and SDW3 confer a GA-insensitive semi-dwarf phenotype comparable in height to the Rht-D1b Green Revolution allele. In field trials, idd5 lines exhibited improved grain weight per spike but were lower-yielding due to reduced spike number.